The Pristine survey IV: approaching the Galactic metallicity floor with the discovery of an ultra-metal-poor star. Issue 3 (18th August 2018) - Starkenburg, Else; Aguado, David S; Bonifacio, Piercarlo; Caffau, Elisabetta; Jablonka, Pascale; Lardo, Carmela; Martin, Nicolas; Sánchez-Janssen, Rubén; Sestito, Federico; Venn, Kim A; Youakim, Kris; Allende Prieto, Carlos; et al.
ABSTRACT: The early Universe presented a star formation environment that was almost devoid of heavy elements. The lowest metallicity stars thus provide a unique window into the earliest Galactic stages, but are exceedingly rare and difficult to find. Here, we present the discovery of an ultra-metal-poor star, Pristine_221.8781+9.7844, using narrow-band Ca H&K photometry from the Pristine survey. Follow-up medium- and high-resolution spectroscopy confirms the ultra-metal-poor nature of Pristine_221.8781+9.7844 ([Fe/H] = −4.66 ± 0.13 in 1D LTE) with an enhancement of 0.3–0.4 dex in α-elements relative to Fe, and an unusually low carbon abundance. We derive an upper limit of A(C) = 5.6, well below typical A(C) values for such ultra-metal-poor stars. This makes Pristine_221.8781+9.7844 one of the most metal-poor stars; in fact, it is very similar to the most metal-poor star known (SDSS J102915+172927). The existence of a class of ultra-metal-poor stars with low(er) carbon abundances suggest that there must have been several formation channels in the early Universe through which long-lived, low-mass stars were formed.